Clinical Evaluation of The Use of PRP as A Treatment for Achilles Tendon Defects in Dog Model - hajar Nisheemi; ashraf. abdulrazaq; Hussain aljabery (Basrah Journal of Veterinary Research)
The Achilles tendon is the most resilient tendon in the musculoskeletal system of canines. It enables the hock to extend, allowing the animal to balance on its toes. Its primary role is to propel the rear limb forward and provide support to the hock. Platelet-rich plasma (PRP), Platelets store growth factors and are crucial in various physiological functions like blood clotting, blood vessel formation, immune defense, and tissue healing. Aim of the study: To analyze and contrast the impacts of Platelet-rich plasma on regeneration of Achilles tendon. Materials and Methods: 10 dogs were divided into two groups: 5 dogs received treatment with Platelet-Rich Plasma (Group A), 5 dogs served as a control (Group B), and left untreated Results: scoring the degree of lameness in dogs that were not treated throughout the entire experiment The control group showed lameness scores, resulting in the animals being unable to lift their legs and take a few steps,The group that was treated with PRP had notably lower levels of lameness and pain throughout the study period,prp treatment resulted in better healing of the injured tendon compared to the untreated group, showing gradual improvement after 7 days. Histologically,PRP enhanced healing with increased cell proliferation, migration and collagen production of tendon-derived cells including increased cellularity and vascularity of ligament tissue ,compared to those in the control group the of the Achilles tendon of the positive control group showed chronic tendonitis. Conclusion: Proved that PRP can greatly enhance tendon repair, tendon growth, and minimize inflammation.